Primary prevention of coronary artery disease among middle aged men in Prague: twenty-year follow-up results - Boudík, F; Reissigová, J; Hrach, K; Tomecková, M; Bultas, J; Anger, Z; Aschermann, M; Zvárová, J (Atherosclerosis, 2006)
BACKGROUND: Coronary artery disease (CAD) represents the most common cause of morbidity and mortality in the Czech Republic. The aim of this study is to analyze long-term cardiovascular diseases (CVD) mortality, identify predictors of outcome and to validate the Framingham risk function in men from the Czech Republic. DESIGN AND METHODS: A 20-year primary prevention study of atherosclerosis risk factors in 1417 men from Prague aged 38-53 years was launched in 1975 (STULONG). RESULTS: When analyzing CVD mortality, heavy smokers had hazard higher than non-smokers and light smokers (p < 0.0001); hypertensives higher than normotensives (p < 0.0001); men with hypercholesterolemia higher than those with normal cholesterol (p = 0.0432), and university-educated men lower than elementary-educated men (p = 0.0006). In 1980-1984, the age specific mortality from CVD in men from STULONG was higher (p = 0.0132) than in the Czech Republic, in 1985-1994 insignificantly lower. The Framingham risk function underestimated the absolute 10-year risk of CAD across the quintile of the risk (p < 0.0001), with 63% discrimination. CONCLUSION: In STULONG, the mortality from CVD was significantly associated with known risk factors (hypertension, smoking, hypercholesterolemia, education); the Framingham risk function underestimated the absolute 10-year risk of CAD.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; obezita; Humans; městské obyvatelstvo; Primary Prevention; lidé středního věku; Hypertension; rizikové faktory; dospělí; primární prevence; lidé; časové faktory; Adult; Follow-Up Studies; Male; Middle Aged; Retrospective Studies; hypertenze; prognóza; incidence; Incidence; Czech Republic; hypercholesterolemie; Hypercholesterolemia; Obesity; retrospektivní studie; Smoking; míra přežití; Česká republika; mužské pohlaví; kouření; Time Factors; Prognosis; následné studie; Urban Population; Risk Factors; Survival Rate